Teoría de crecimiento económico: un debate inconcluso - Rosende, Francisco (Estudios de Economía, 2016)
This paper provides a wide-ranging overview of recent research in economic growth theory that emphasizes the importance of the response of economic growth process to changes in global productivity (GP). The research agenda for the next years should be oriented towards the elaboration of a satisfactory theory of GP changes. This requires a consensus on the methodology used to measure it.